2018
DOI: 10.1017/s0022377818001046
|View full text |Cite
|
Sign up to set email alerts
|

On the breakdown modes and parameter space of ohmic tokamak start-up

Abstract: Tokamak start-up is strongly dependent on the state of the initial plasma formed during plasma breakdown. We have investigated through numerical simulations the effects that the pre-filling pressure and induced electric field have on pure ohmic heating during the breakdown process. Three breakdown modes during the discharge are found, as a function of different initial parameters: no breakdown mode, successful breakdown mode and runaway mode. No breakdown mode often occurs with low electric field or high pre-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 70 publications
1
30
0
Order By: Relevance
“…2016; Peng et al. 2018), we have found that the breakdown can be divided into three phases: fast avalanche, transition and slow avalanche. From this figure, three phases can be figured out clearly, showing in figure 2( b – d ), respectively.…”
Section: Simulation Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…2016; Peng et al. 2018), we have found that the breakdown can be divided into three phases: fast avalanche, transition and slow avalanche. From this figure, three phases can be figured out clearly, showing in figure 2( b – d ), respectively.…”
Section: Simulation Resultsmentioning
confidence: 94%
“…In this work a PIC-MCC method (Lapenta, Brackbill & Ricci 2006) is used. This method which was developed previously has been applied to different plasma areas, such as microdischarges in the low-temperature plasma , magnetized capacitively coupled plasma (Yang et al 2017a,b;) and fusion plasma (Jiang et al 2016;Peng et al 2018).…”
Section: Description Of the Modelmentioning
confidence: 99%
See 3 more Smart Citations